BILOLOGICAL STUDY OF JOHNSONGRASS (Sorghum halepense L.) RHIZOMES - T. Al-Hially (Mesopotamia Journal of Agriculture)
The experiment was conducted out under the conditions of the greenhouse at the Field of Crop Science, Mosul University on 2012. The aim of the research is to study the effect of length and diameter of Johnsongrass rhizomes planted at different densities on the regeneration and produce shoots and roots at the ends of both cutting rhizome. The study included three factors, rhizome diameter < 4mm and < 3mm, number of buds on the rhizome cutting i.e (1, 2, 3 buds) and the third factor was planting densities at (2, 4, 8) rhizome segments in each pot. The experiment was set out as factorial system using complete randomized design with three replicates. The results clearly showed that none of the segments of one bud and with <3mm diameter and whether they were planted at densities of 2 or 4 cuttings were survived and the chances of survival segments were found to be proportional to their initial length up to 6 cm and diameter up to < 4mm in which the percentage of survival increased to 80%. Moreover it was observed that increasing the levels of the three factors led to a significant increase in the mean of plant height, number of leaves, the dry weight of leaves and roots